Analisis Pengaruh Inflasi dan Kurs Dolar terhadap Harga Saham BRI Syariah - Muzdalifah Muzdalifah (FOCUS, 2022)
Investment using the capital market is one of the investments that are in demand by every country. By maintaining a stable political condition and currency value, it can indirectly make investments in a country last longer. The same is the case with the economic conditions in Indonesia during the covid-19 pandemic. Indonesia is really struggling how to maintain the country’s economic conditions so that it continues to run during the pandemic which generally make people’s lives and economy decline. One of the conditions that describe this economic condition can be seen from the inflation rate and also the rupiah exchange rate to us dollar. The purpose of this study is to analize the effect on inflation and also the value of the US dollar exchange rate on the stock price of an Islamic Banking. Where in this study will conduct research on BRI Syariah which has long existed in the Islamic Capital Market (Jakarta Islamic Index). This study intends to examine the effect of inflation and the rupiah exchange rate to US dollar on the stock price of BRI Syariah. The method used  is the Uji Classic assumtion test, including the Normality test, multicollinearity test, Autocorrelation test and heteroscedasticity test. Meanwhile, in analyzing the data using SPSS 21, the resulths of multiple linier regression where obtained because the significance value was 0,00 which is smaller than 0,05. This means that inflation (X1) has an effect on the stock price (Y) of BRI Syariah while the significance value of the US Dollar Exchange (X2) 0,202 > 0,05, this means that the US Dollar Exchannge rate has no effect on the stock price of BRI Syariah (Y).